Language Switching Makes Pronunciation Less Nativelike. (April 2014) - Goldrick, Matthew; Runnqvist, Elin; Costa, Albert
It is well known that multilingual speakers' nonnative productions are accented. Do these deviations from monolingual productions simply reflect the mislearning of nonnative sound categories, or can difficulties in processing speech sounds also contribute to a speaker's accent? Such difficulties are predicted by interactive theories of production, which propose that nontarget representations, partially activated during lexical access, influence phonetic processing. We examined this possibility using language switching, a task that is well known to disrupt multilingual speech production. We found that these disruptions extend to the articulation of individual speech sounds. When native Spanish speakers are required to unexpectedly switch the language of production between Spanish and English, their speech becomes more accented than when they do not switch languages (particularly for cognate targets). These findings suggest that accents reflect not only difficulty in acquiring second-language speech sounds but also the influence of representations partially activated during on-line speech processing.